A Robot to Monitor Nuclear Facilities: Using Autonomous Radiation-Monitoring Assistance to Reduce Risk and Cost - Bird, Benjamin; Griffiths, Arron; Martin, Horatio; Codres, Eduardo; Jones, Jennifer; Stancu, Alexandru; Lennox, Barry; Watson, Simon; Poteau, Xavier (IEEE robotics & automation magazine, 2019)
Nuclear facilities often require continuous monitoring to ensure there is no contamination of radioactive materials that might lead to safety or environmental issues. The current approach to radiological monitoring is to use human operators, which is both time consuming and cost inefficient. As with many repetitive, routine tasks, there are considerable opportunities for the process to be improved using autonomous robotic systems.